ChemInform Abstract: Synthesis of 2‐(Benzylthio)‐4‐(trifluoromethyl)thiazole‐5‐carboxylates Using S‐Benzylisothiouronium Halides as Thiol Equivalents. Issue 51 (December 2015) - Hickey, Shane M.; White, Jonathan M.; Pfeffer, Frederick M.; Ashton, Trent D.
Abstract: S‐Benzylisothiouronium halides (II) obtained by reaction of thiourea and benzyl halides are used as odorless, stable thiol equivalents in the synthesis of 2‐benzylthio‐derivatives of type (III).